Ligament and Tendon Repair through Regeneration Using Mesenchymal Stem Cells - Ramdass, Bharathi; S. Koka, Prasad (Current Stem Cell Research & Therapy, 2015)
One of Nature’s gifts to mankind is mesenchymal stem cells (MSC’s). They are multipotent in nature and are present literally in every tissue. Since, they possess certain characteristics of stem cells such as self-renewal and differentiation they are known to be one of the key players in normal tissue homeostasis. This novel function of mesenchymal stem cells has been explored by scientists in the field of regenerative medicine. This review gives an insight of the various sources of mesenchymal stem cells available for tissue engineering with regard to tendon and ligament and the mechanism involved during regeneration.
Keywords: tendon and ligament